Dampak Proses Pembelajaran Daring di Tengah Pandemi Covid-19 pada Pembelajaran PPKN di Kelas X IPA 2 - Silvia Anggreni BP; Ade Kurnia; Shinta Kurnia Izati (IJOCE: Indonesia Journal of Civic Education, 2022)
This study aims to find out how the impact of the courageous learning process in the midst of the covid-19 pandemic on Civics subjects and to find out the teacher's efforts in overcoming the negative impact of daring to study in the midst of the Covid-19 pandemic in class X IPA 2 SMA N 1 Payakumbuh Regency. The research method uses a qualitative approach with a descriptive method. The informants of this study were 2 PPKn subject teachers, 6 parents, 6 students and 6 students of class X IPA 2. The data collection technique used purposive sampling technique in collaboration with snowball sampling. The types and sources of data are primary data and secondary data. The results showed that the impact of the online learning process in the midst of the Covid-19 pandemic on Civics Class subjects, namely: a). Positive impact and negative impact. The conclusion of the research is that the impact of online learning is: teachers and parents work together in overcoming online learning. Teachers must also be good at adjusting teaching methods while online. Keywords: Covid-19, Online, PPKn Learning